The Influence of Breakfast Quality on Blood Sugar Levels of Clients with DM Type 2 - Christiany, Irine; Waloya, Kiaonarni Ongko; Mu’afiro, Adin (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Breakfast quality is an overview of diet and food composition which client with DM Type2 aims to find theright type, amount, and schedule as the principles of diet for DM to keep the blood sugar levels stable. Theresearch method was cross sectional study. The population was all patients in Geriatric Unit of Gundih PublicHealth Center in Surabaya who already diagnosed with DM Type2, taken randomly (simple random sampling).Dependent variable was blood sugar levels of client with DM Type2. Independent variable was the quality ofbreakfast. The research instrument was a questionnaire and a food recall 1 x 24 hours. Data analysis was usinglogistic regression test. The results of the analysis of data showed that the blood sugar levels of the clients withDM Type 2 was influenced by the amount and schedule of breakfast.